Comparison of Effectiveness of Supervised Exercise Program and Cyriax Physiotherapy in Patients with Tennis Elbow (Lateral Epicondylitis): A Randomized Clinical Trial. (2nd May 2012) - Viswas, Rajadurai; Ramachandran, Rejeeshkumar; Korde Anantkumar, Payal
Abstract : Objective . To compare the effectiveness of supervised exercise program and Cyriax physiotherapy in the treatment of tennis elbow (lateral epicondylitis). Design . Randomized clinical trial. Setting . Physiotherapy and rehabilitation centre. Subjects . This study was carried out with 20 patients, who had tennis elbow (lateral epicondylitis). Intervention . Group A (n = 10 ) had received supervised exercise program. Group B (n = 10 ) was treated with Cyriax physiotherapy. All patients received three treatment sessions per week for four weeks (12 treatment sessions). Outcome measures . Pain was evaluated using a visual analogue scale (VAS), and functional status was evaluated by completion of the Tennis Elbow Function Scale (TEFS) which were recorded at base line and at the end of fourth week. Results . Both the supervised exercise program and Cyriax physiotherapy were found to be significantly effective in reduction of pain and in the improvement of functional status. The supervised exercise programme resulted in greater improvement in comparison to those who received Cyriax physiotherapy. Conclusion . The results of this clinical trial demonstrate that the supervised exercise program may be the first treatment choice for therapist in managing tennis elbow.